Burning modes of dc low pressure discharge with a transverse constriction - Lisovskiy, V.A.; Ogloblina, P.A.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2015)
This paper reports the current-voltage characteristics (CVCs) of dc discharge in different modes of burning we registered for several values of the transverse constriction diameter in a broad nitrogen pressure range. Existence conditions for normal and abnormal modes are determined. The CVCs are shown to possess a hysteresis for discharge tubes with constrictions at nitrogen pressure of 0.05 and 0.1 Torr. At higher pressure of 0.3 Torr the constriction does not actually affect the discharge CVC. For the pressure of 5 Torr a positive column is observed in the anode part of the tube what enables one to support discharge burning at lower voltage values across the electrodes.